2014
DOI: 10.1371/journal.pone.0089322
|View full text |Cite
|
Sign up to set email alerts
|

Sinks for Inorganic Nitrogen Deposition in Forest Ecosystems with Low and High Nitrogen Deposition in China

Abstract: We added the stable isotope 15N in the form of (15NH4)2SO4 and K15NO3 to forest ecosystems in eastern China under two different N deposition levels to study the fate of the different forms of deposited N. Prior to the addition of the 15N tracers, the natural 15N abundance ranging from −3.4‰ to +10.9‰ in the forest under heavy N deposition at Dinghushan (DHS), and from −3.92‰ to +7.25‰ in the forest under light N deposition at Daxinganling (DXAL). Four months after the tracer application, the total 15N recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
7
27
2
Order By: Relevance
“…2c) in the upper Jiaojiang watershed, wood product export, and forest biomass storage may account for a considerable proportion of the N imbalance. Assuming that~15 % of NANI (or 33 % of atmospheric N deposition) was exported by wood products and forest biomass storage as observed in eastern China (Sheng et al 2014), denitrification would by difference account for the fate of~51 % of NANI in the upper Jiaojiang watershed. This denitrification percentage is similar to the sum of agricultural land denitrification (i.e., 36-4 % of total N applied) (Yan et al 2011;Ti and Yan 2013) and in-stream denitrification (i.e., 10-35 % of total N input to rivers) (Yan et al 2011;Chen et al 2012) in the surrounding region.…”
Section: Discussion Efficiency Of the Lagged Variable Modelmentioning
confidence: 99%
“…2c) in the upper Jiaojiang watershed, wood product export, and forest biomass storage may account for a considerable proportion of the N imbalance. Assuming that~15 % of NANI (or 33 % of atmospheric N deposition) was exported by wood products and forest biomass storage as observed in eastern China (Sheng et al 2014), denitrification would by difference account for the fate of~51 % of NANI in the upper Jiaojiang watershed. This denitrification percentage is similar to the sum of agricultural land denitrification (i.e., 36-4 % of total N applied) (Yan et al 2011;Ti and Yan 2013) and in-stream denitrification (i.e., 10-35 % of total N input to rivers) (Yan et al 2011;Chen et al 2012) in the surrounding region.…”
Section: Discussion Efficiency Of the Lagged Variable Modelmentioning
confidence: 99%
“…A positive correlation between soil CO 2 flux and soil NO 3 − -N content is generally observed at large spatial scales (Koba et al 2003;Inselsbacher et al 2010). Based on a 15 N tracer experiment in the subtropical forests of southern China, Sheng et al (2014) also reported that more 15 NH 4 + was recovered from organic and mineral soils, while a large proportion of 15 NO 3 − was recovered from plant roots. In the early stage of N saturation, most of the deposited N is sequestered within the vegetation biomass (Bowden et al 2004), and the increased C allocation to root systems could increase autotrophic respiration.…”
Section: Effects Of N Levels and Forms On Soil Co 2 Fluxmentioning
confidence: 99%
“…On the contrary, deposited NO 3 − is very mobile and is absorbed by plants and soil microbes (Inselsbacher et al, 2010). Based on a 15 N tracer experiment in the subtropical forests of southern China, Sheng et al (2014) also reported that more 15 NH 4 + was recovered from organic and mineral soils, while a large proportion of 15 NO 3 − was recovered from plant roots. In the early stage of N saturation, most of the deposited N is sequestered within the vegetation biomass (Bowden et al, 2004), and the increased C allocation to root systems could increase autotrophic respiration (Kou et al, 2015).…”
Section: Effects Of Simulated N Deposition On Soil Co 2 Emissionmentioning
confidence: 99%
“…The subtropical plantation forests are vulnerable to increased N deposition due to single community structure and barren soil fertility. Previous studies show that simulated NH 4 NO 3 inputs to the subtropical forests significantly inhibit litter decomposition and soil CO 2 emission (Fang et al, 2007;Mo et al, 2008), decrease CH 4 uptake (Zhang et al, 2008b(Zhang et al, , 2012b, and increase gaseous N emission (N 2 O, NO, and N 2 ) (Zhang et al, 2008a(Zhang et al, , 2009 (Sheng et al, 2014). The contrasting effects of N cumulation on root autotropical respiration and microbial heterotropical respiration dominate the reponses of soil CO 2 flux to N addtion .…”
Section: Introductionmentioning
confidence: 99%